The Thematical Classification of Arabic Proper Nouns Used in the Work of «The Stories of Prophets» by Rabghuzy - Dilfuza Sagdullaeva Karimullaevna (Zien Journals, 2022)
This article analyses the separated lexical groups of words and phrases of Arabic origin, defined in the work of Qisasi Rabguzi by Nasuriddin Rabguzi, first written in Turkic language based on Islamic sources in the XIII-XIV centuries in Khorezm. Several kinds of proper names, being effectively used in the language of the work, were identified. It was also concluded that borrowed and exotic anthroponyms, ethnonyms, theonyms and toponyms and religious vocabulary are the most frequently used groups in the language of the work. This research plays an important role in the study of the historical development of the process of borrowing Arabic words and lexical composition in the language of the Turkic peoples of the XIII-XIV centuries.
Keywords: lexical content; arabic loanwords; proper nouns; vocabulary